2019
DOI: 10.1145/3361218
|View full text |Cite
|
Sign up to set email alerts
|

Eye, Head and Torso Coordination During Gaze Shifts in Virtual Reality

Abstract: Humans perform gaze shifts naturally through a combination of eye, head and body movements. Although gaze has been long studied as input modality for interaction, this has previously ignored the coordination of the eyes, head and body. This article reports a study of gaze shifts in virtual reality aimed to address the gap and inform design. We identify general eye, head and torso coordination patterns and provide an analysis of the relative movements’ contribution and temporal alignment. We quantify effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 76 publications
7
84
0
Order By: Relevance
“…This has been observed to lead to less eye rotation and a comparatively larger contribution of head movement to gaze shifts [Kollenberg et al 2010;Pfeil et al 2018]. For this work, we specifically built on quantitative insight into eye, head and torso coordination from a recent study of gaze shifts in VR [Sidenmark and Gellersen 2019a]. That work informs the criteria we use to filter gestural head movement from head movement that is naturally coupled with gaze.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed to lead to less eye rotation and a comparatively larger contribution of head movement to gaze shifts [Kollenberg et al 2010;Pfeil et al 2018]. For this work, we specifically built on quantitative insight into eye, head and torso coordination from a recent study of gaze shifts in VR [Sidenmark and Gellersen 2019a]. That work informs the criteria we use to filter gestural head movement from head movement that is naturally coupled with gaze.…”
Section: Related Workmentioning
confidence: 99%
“…Natural head movements are used to further the range of the eyes or to move the eyes into a comfortable position [Tweed et al 1995]. Research has shown natural head movement occurs at the same time as, or a shortly after, the initial eye movement to maintain a comfortable eye-in-head position [Sidenmark and Gellersen 2019a]. If the head does not move within a certain time (t l ) after an eye movement we can assume that the head movement is gestural.…”
Section: Bimodalgazementioning
confidence: 99%
“…In order to deeply understand visuo-motor behavior based on eye movement and driving data in an effective and controllable way, virtual reality is used in this paper, as has been done in many works [22]. A virtual environment ( VE ), including common straight, curved roads and buildings, is designed for the experimental study.…”
Section: Methodsmentioning
confidence: 99%
“…The entire concept of (HMD) VR relies on continuous head rotation tracking, making rotation a suitable user interface through the use of a crosshair that fixates eye gaze and synchronizes it (at least to same degree) with head rotation. In fact, human-computer interaction research has shown that head rotation provides an adequate proxy measure of eye gaze: gaze tends to focus around a rotation-controlled crosshair, and gaze shifts above 25°are typically accompanied by subsequent head movement with a lag of 30-150 ms (Sidenmark and Gellersen 2020). In general, head rotation data has seen very few published clinical applications beyond its immediate role in graphical presentation, either as a way of adapting the virtual environment (e.g., prompting a "Look up!"…”
Section: Full Immersion Through Innovative User Interfaces and Makingmentioning
confidence: 99%